Technology to improve sports performance in wheelchair sports - Laferrier, J. Z.; Rice, I.; Pearlman, J.; Sporner, M. L.; Cooper, R.; Liu, T.; Cooper, R. A. (Sports Technology, 2012)
Sport and recreation are cornerstones of how we define ourselves as human beings and the competitive spirit is just as prominent in individuals with disabilities as it is in their able-bodied counterparts. Wheelchair sports were initially developed following WWII as a rehabilitation tool to care for the young men and women injured during the war. Today athletes with disabilities are narrowing the gap in competition between the impaired and the unimpaired through training, advancement of technology, and the competitive spirit and ingenuity of the seated athlete. This article examines a number of factors related to maximizing performance and the prevention of injury in wheelchair sport. Physical and technological considerations for various wheelchair sports will be discussed including; metabolic demands, equipment selection, configuration, advances in technology and performance measurement as well as directions for future research.